Molecular evidence from ascidians for the evolutionary origin of vertebrate cranial sensory placodes. - Mazet, F; Shimeld, S (2005)
Cranial sensory placodes are specialised areas of the head ectoderm of vertebrate embryos that contribute to the formation of the cranial sense organs and associated ganglia. Placodes are often considered a vertebrate innovation, and their evolution has been hypothesised as one key adaptation underlying the evolution of active predation by primitive vertebrates. Here, we review recent molecular evidence pertinent to understanding the evolutionary origin of placodes. The development of vertebrate placodes is regulated by numerous genes, including members of the Pax, Six, Eya, Fox, Phox, Neurogenin and Pou gene families. In the sea squirt Ciona intestinalis (a basal chordate and close relative of the vertebrates), orthologues of these genes are deployed in the development of the oral and atrial siphons, structures used for filter feeding by the sessile adult. Our interpretation of these findings is that vertebrate placodes and sea squirt siphon primordia have evolved from the same patches of specialised ectoderm present in the common ancestor of the chordates.